2018
DOI: 10.32413/pjph.v8i2.118
|View full text |Cite
|
Sign up to set email alerts
|

Awareness About Indoor Air Pollution in General Population of Rawalpindi and Islamabad

Abstract: Background: Indoor air pollutants are increasingly being associated with respiratory illnesses leading to high degree of morbidity and mortality. There are not sufficient epidemiological studies from Pakistan which assess level of awareness of indoor air pollution resulting in respiratory diseases in population. Methods: This cross sectional survey was carried out on general population of Rawalpindi/Islamabad. Sample size was 223 study subjects selected by non-probability convenient sampling. Knowledge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Approximately 20% of the study women understood the cause of IAP was due to poor ventilation which was four times lower than a previous study conducted in Pakistan in 2018 [10]. Approximately 90% of the participants were known of some methods to reduce IAP exposure in Rural Pakistan among women rather than the vast majority of more than nine in ten were aware of the availability of clean fuel such as LPG, and they have expressed willingness to switch it.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Approximately 20% of the study women understood the cause of IAP was due to poor ventilation which was four times lower than a previous study conducted in Pakistan in 2018 [10]. Approximately 90% of the participants were known of some methods to reduce IAP exposure in Rural Pakistan among women rather than the vast majority of more than nine in ten were aware of the availability of clean fuel such as LPG, and they have expressed willingness to switch it.…”
Section: Discussionmentioning
confidence: 82%
“…As the result of our study, only half of the participants have shown knowledge of preventive measures of IAP among women. Similarly, in a similar study, those who knew about IAP was detrimental to health were 95%, and there was an association between IAP and respiratory diseases [10]. This is due to the lack of awareness of the harmful effects of polluting indoor air.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Tariq et al [160] reported that PM 2.5 , formaldehyde, and CO were responsible for chronic respiratory diseases such as breath shortening, bronchitis, and asthma in Karachi. Aslam et al [161] scrutinized the effects of indoor polychlorinated biphenyls on human health in the Pakistani population.…”
Section: Major Health Hazards Of Indoor Air Contaminationmentioning
confidence: 99%
“…Because the level of visible pollution indoors is relatively low, indoor air quality has received significant attention in recent years. In total, IAP is estimated to be responsible for about 2.7% of the global disease burden, and 1.6 million deaths occur each year for the same reason (Tariq et al, 2018;Wong-Parodi, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%